Investigation of the influence of stabilizers on the viscosity of the recovered mixture of a hypertonic drink for athletes - Bochkarev, Sergiy; Mazaeva, Viktoria; Ovsiannikova, Tetiana; Zviahintseva, Oksana (Scientific Route OÜ, Tallin, Estonia, 2020)
When introducing plant and animal protein products, in addition to nutritional value, it is advisable to assess their physicochemical properties and technological indicators, in particular, homogeneity and consistency stability. The aim of research is to determine the effect of consistency stabilizers on the viscosity of reconstituted hypertonic drink for athletes based on flaxseed cake, sesame seeds and whey protein concentrate.The mass fraction of protein in the model dry mixture of a hypertonic drink, as well as in its individual components by the Kjeldahl method, the mass fraction of fiber – by the gravimetric method, the mass fraction of lipids – by the extraction-gravimetric method, the mass fraction of moisture – by the thermogravimetric method. The mass fraction of ash in the mixtures was carried out by the method of incineration followed by calcining the mineral residue at a temperature of 450 ... 600 °C. The effective viscosity in the reduced samples of mixtures without and with the addition of stabilizers was determined on a rotational viscometer "Rheotest 2". For the planning of the experiment and data processing, mathematical methods were applied using the Microsoft Office Excel 2003 software package.The chemical composition of individual components and a model dry mixture of a hypertonic drink for the nutrition of athletes, including the content of compounds that have a stabilizing effect on the restored product, has been investigated. It has been proved that the effective viscosity of the reconstructed model mixture in comparison with the effective viscosity of the individual components of the mixture nonaditively increases. The mutual influence of the consistency stabilizers (gum arabic (E 414) and carboxymethylcellulose (E 466)) on the val-ue of the effective viscosity of the reconstituted hypertonic drink was investigated. The developed model mixture of a hypertonic drink is recommended to be used for the development of competitive dry mixtures of hypertonic drinks of plant and animal origin for the nutrition of athletes.
Keywords: dry mixture; hypertonic drink; whey protein; effective viscosity; consistency stabilizers; flax-seed cake; sesame cake